The social integration of demobilised ex-combatants in Mozambique. - Taju, Gulamo Amade (My University, 1998)
This study is an analysis of the social integration of demobilised soldiers in Mozambique, in the context of post-war social reconstruction. De-constructing the concept of "reintegration" that informed the top-down programmes designed for the social integration of ex-combatants, that dichotomize society into the military sphere and the civilian one, so that the process into which ex-combatants are involved after leaving the Army is one of "returning home", as society remaining the same or in a moving equilibrium, one saw society- marked by social differentiations, even amongst the demobilised ex-combatants. The ideal of "sameness" between "civilians" and ex-combatants involved in the concept of reintegration seems more an utopia. This research used previous studies of my colleagues. In criticizing them, I do not wish to create the impression that these works are of little value. Their analysis stand from very different disciplinary approaches, and with others aims. The major weakness I often saw was the indefinition of the terms they use and the mix of concepts like social integration and reintegration as having the same meaning. Other documentary research was carried out, and as the study included the understanding of meanings, values, individual actions and social interactions, in order to capture the meaningfulness of such life other qualitative methods were employed as the informal interviews, the use of key informants, participation in and observation of events in the setting. Looking society in a dynamic change, social integration is regarded as the process of negotiation of a common social order between actors in interaction (demobilised soldiers, other social groupings, and institutions like the state). It is better approached using the concept of integration. As an interactive process it is marked by a tension between the affirmation of the individuality of actors and the will to the sense of community. In its course different actors mobilise and use different identities according to the situations. avoiding or erasing specificities of previous socializations and identities and highlighting others. This study is an analysis of the social integration of demobilised soldiers in Mozambique, in the context of post-war social reconstruction. De-constructing the concept of "reintegration" that informed the top-down programmes designed for the social integration of ex-combatants, that dichotomize society into the military sphere and the civil one, so that the process into which ex-combatants is one of "returning home", as society remaining the same or in a moving equilibrium, one saw society full of differentiations, even within the groups social defined as "demobilised soldiers". The ideal of "sameness" involved in the concept of reintegration seems more an utopia. Society is full of social differentiation, and the group of demobiIised soldiers also inmarked by differences of gender, age, marital status, previous military affiliation and rank, control of resources and social status in the living/working place, marital status. This study used previous studies of my colleagues. In criticizing them, I do not wish to create the impression that these works are of little value. Their analysis stand from very different disciplinary approaches, and with others aims. The major weakness I often saw was the indefinition of the terms they use and the mix of concepts like social integration and reintegration as having the same meaning. Other documentary research was carried out, and as the study included the understanding of meanings, values, individual actions and social interactions, to capture the meaningfulness of such life other qualitative methods were employed: informal interviews, the use of key informants, participation in and observation of events in the setting. Looking society in a dynamic change, the process of negotiation of a social order between actors in interaction (demobilised soldiers, other social groupings, and institutions like the state) is better approached using the concept of social integration. As an interactive process, in its course different actors mobilise and use different identities, the most convenient for each occasion, in a way that sometimes involves the attempt to erase specificities of previous socializations and identities.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg. in partial fulfilment of the requirements for the degree of Master of Arts
Keywords: Mozambique -- Politics and government -- 1975; Armed forces -- Mozambique -- Demobilization.; Mozambican Demobilised Soldiers Association.; National liberation movements -- Mozambique.